Association Between Hyperaldosteronemia and Electrophysiological Myocardial Activity in Heart Failure with Preserved Ejection Fraction - A. N. Shevelok (SINAPS LLC, 2020)
Background. Sudden cardiac death, one of the most common types of cardiac death, is most often triggered by ventricular arrhythmia. Plasma aldosterone level has been shown to be an independent risk factor of life-threatening ventricular arrhythmia in patients with left ventricular systolic dysfunction following acute myocardial infarction. Whether either effect also occurs in patients with heart failure and preserved ejection fraction is currently unknown. Purpose. The study aims to investigate the relationship between plasma aldosterone level and ventricular arrhythmias in longterm heart failure with preserved ejection fraction. Methods. A cross-sectional study included 158 patients (58 men and 100 women, mean age 62.3±7.4 years) with heart failure with preserved ejection fraction (> 50%). Patients had no history of primary aldosteronism and did not use the mineralocorticoid receptor antagonists during the last 6 weeks. Aldosterone plasma level was measured and 24-hour electrocardiographic monitoring was performed. Results. According to laboratory results 99 patients (62.7%, 95% confidence interval 55.0-70.0%) had normal (40-160 pg/ml) aldosterone plasma level (nAld) and 59 patients (37.3%, 95% CI 30.0-45.0%) had high (> 160 pg/ml) aldosterone level (hAld). hAld patients more often had QTc prolongation (44.1% versus 18.2%) and ventricular arrhythmias (83.1% vs 61.6%) compared to nAld patients (all Ps <0.001). The number of ventricular premature complexes in 24 hours were higher in hAld group (median 214, range 64-758) compared to nAld (median 52, range 16-198, P < 0.003). hAld patients more often occurred bigemy, couple ventricular ectopy and nonsustained ventricular tachycardia (39.0% vs 19.0%, р=0.01). In Cox regression model's high aldosterone plasma level was the independent risk factors of QTc prolongation (odds ratio 1.6, 95% confidence interval 1.1-5.7, p=0.034) and prognostically unfavorable ventricular arrhythmias (odds ratio 1.8, 95% confidence interval 1.2-6.8, p=0.024). Conclusion. In long-term HFpEF plasma aldosterone level is significantly related to QTc prolongation as well as ventricular arrhythmias.